Investigação da ocorrência de eventos epigenéticos em Haemonchus contortus e sua relação com a resistência ao anti-helmíntico monepantel - Moraes, Caroline Valério (2019)
Parasitism by gastrointestinal nematodes, mainly by Haemonchus contortus, is the major obstacle to sheep production. Anthelmintic treatment is the main method used by farmers to control worms. However, parasites acquire resistance and, currently, monepantel is the most effective available anthelmintic to control parasites in small ruminant flocks. This study investigated the epigenetic events in H. contortus involved on its development as well as in the establishment of monepantel resistance. Since epigenetics, such as DNA methylation and histone modifications, contribute to phenotypic variation, its importance for parasite physiology and development of resistance still needs to be clarified. In silico analyses suggested that DNA methylation does not occur in H. contortus, but we detected tRNA methylation and post-translational histone modifications, which were confirmed by ELISA in infective larvae (L3). By reverse transcription quantitative PCR (RT-qPCR) assays, changes in gene expression were detected for dnmt, hmt and tfjmj, which are genes potentially related to the epigenetic machinery, during the life cycle of H. contortus (eggs, L3 larvae and adults). An increase in transcript abundance for dnmt and hmt genes in adult females compared to males was also observed. In addition, the expression of these genes was not affected by the resistance status to monepantel, in L3 larvae. In the comparison between monepantel susceptible and resistant H. contortus isolates, no changes in mptl1 gene expression nor the presence of two mutations described in literature (intron 15 retention and loss of exon 12 in mptl1) were detected. The results obtained here are relevant to gain knowledge related to epigenetic events in parasites. In addition, since the transcription levels of genes from the epigenetic machinery were changed during the life cycle of H. contortus, they appear to be determinant for worm development and adaptation to environmental conditions (inside and outside the host), and can be further investigated as potential new drug targets for nematode control.